Use of European Experience in the Introduction of Digital Service Tax in New Uzbekistan - Abdullaev Asliddin Junaydullaevich; Ashurov Sherzod Rakhimovich (Universitas Muhammadiyah Sidoarjo, 2022)
The article discusses the main aspects of social security and threats, as well as the specifics of social security in Uzbekistan. The development of the digital economy has led to a sharp increase in the amount of information needed to make management decisions in the economy at different levels. Ultimately, the knowledge of staff and the development of information and communication technologies in the national economy show an increase in its level of development and competitiveness